(untitled) (Journal of Pedagogical Inventions and Practices, 2022)
Recently, a whole range of challenges have arisen in relation to education. This was influenced by the introduction of new technologies, the emergence of new professions and the departure of old professions, as well as the increasing influence of information flows, competition, the growth of the formation of lifestyles, as well as the very goals of education. That is, in this case, education has entered the position when it has ceased to suit everyone. For example, if under the Soviet Union everyone sought to educate their children and in the absence of a diploma of higher education it was practically impossible to work anywhere, then in the modern world it is very important to educate not an educated, but an independent person. And in most cases, we can observe how teenagers are already starting to earn a lot of money through social networks, without having any education yet. And in order to recreate the popularization of education, it is necessary to introduce globalization into education through modern methods.